2020
DOI: 10.1371/journal.pone.0242256
|View full text |Cite
|
Sign up to set email alerts
|

No association between the vitamin D-binding protein (DBP) gene polymorphisms (rs7041 and rs4588) and multiple sclerosis and type 1 diabetes mellitus: A meta-analysis

Abstract: Background The association between polymorphisms in vitamin D-binding protein (DBP) gene and the risk of multiple sclerosis (MS) and type 1 diabetes mellitus (T1DM) has been investigated in many studies, but the studies showed controversial results. The rationale for this meta-analysis was to determine whether DBP polymorphisms increases the risk of MS and T1DM by pooling data. Methods Potentially relevant studies were searched using GWAS Catalog, PubMed, Embase, CNKI and WANFANG databases up to November 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The meta-analysis of the five studies presented showed no association between rs7041 and rs4588 polymorphisms with the risk of T1D [62].…”
Section: Diabetes Type 1 (T1d)mentioning
confidence: 75%
See 1 more Smart Citation
“…The meta-analysis of the five studies presented showed no association between rs7041 and rs4588 polymorphisms with the risk of T1D [62].…”
Section: Diabetes Type 1 (T1d)mentioning
confidence: 75%
“…Langer-Gould et al suggested that these differences cannot be explained by racial/ethnic variations in bioavailable vitamin D [92]. Xin Zhang et al provide evidence that VDBP rs7041 and 4588 polymorphism may not be associated with an increased risk of multiple sclerosis in the meta-analysis [62].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…The VDBP allele frequency in our study subjects was similar to previously reported Korean genotyping results ( 19 ), and no significant differences were observed between T1DM and controls. A recent meta-analysis reported no significant association between VDBP polymorphisms and T1DM risk ( 39 ). Because all of our subjects were the same race and the sample size was too small, we could not analyze the role of VDBP polymorphisms in the development of T1DM or DKA.…”
Section: Discussionmentioning
confidence: 99%
“…The missense variant, rs7041, located in the Gc gene and that resulted significantly associated in our analysis with Gc plasma levels, has been consistently found to be associated with serum Gc levels as well as vitamin D levels [ 43 , 63 , 64 ]. This SNP did not result associated with MS in [ 65 , 66 ], but a protective effect of the C allele on MS risk was found in [ 67 ] as this allele was also linked to higher serum vitamin D levels. The intronic variant rs10455872 is located on the lipoprotein(a) ( LPA ) gene, and the G allele has been previously strongly linked to increased plasma lipoprotein(a) [Lp(a)] levels [ 68 ].…”
Section: Discussionmentioning
confidence: 99%